2009
DOI: 10.1590/s1807-59322009000900008
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in the Late Follow-Up of Ulcerative Colitis Patients Submitted to Restorative Proctocolectomy with Sphincter Preservation Over Ten Years Ago

Abstract: OBJECTIVETo evaluate, by means of the Inflammatory Bowel Disease Questionnaire (IBDQ), the quality of life of ulcerative colitis patients submitted to proctocolectomy with sphincter preservation using J-pouch reconstruction over ten years ago.METHODSThe study consisted of 36 patients interviewed using the Inflammatory Bowel Disease Questionnaire. The score scale, resulting from the addition of each answer, ranged from 32 to 224, where the highest score indicates the best quality of life. The chi square test wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
3
10
0
1
Order By: Relevance
“…1,6,7,13,21 Our study found that younger age at the time of colectomy, diagnosis, and survey show better QOL than older age. Females have lower sexual function and fertility, while males have decreased sexual function but appear capable of conceiving a child.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…1,6,7,13,21 Our study found that younger age at the time of colectomy, diagnosis, and survey show better QOL than older age. Females have lower sexual function and fertility, while males have decreased sexual function but appear capable of conceiving a child.…”
Section: Discussionmentioning
confidence: 54%
“…We reported patient’s total QOL scores based on classification by Meyer et al (≥200=excellent, 101-199=good or regular, ≤100=bad). 13 Two additional categories, bowel anastomosis function (pouchitis, accidental leakage and urge for defecation) and reproductive health (infertility, conception and sexual function), were included in a supplemental questionnaire (see online-only Appendix, http://links.lww.com/MPG/A108) that included quantitative questions such as number of children and episodes of Pouchitis. Subjects under age 18 at the time of the survey were interviewed the same as other participants except they were not asked questions regarding sexual function.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-TNF biological drugs are a landmark in the treatment of inflammatory bowel disease, especially infliximab and adalimumab [5][6][7][8][9][10][11][13][14][15][16][17][18][19][20][21][22] . The anti-TNFs promote healing of the inflamed intestinal mucosa with reduction in the local inflammatory process, erosions, and ulcerations 5,16 .…”
Section: Discussionmentioning
confidence: 99%
“…The construction of a questionnaire should be formulated in such a way as to present questions respecting the principles of clarity, coherence and neutrality. The writing of the questions should use clear and comprehensible language, avoiding complex, ambiguous and too long questions 25,27 .…”
Section: Construction Of Research Instrumentsmentioning
confidence: 99%